Intraoperative completion cone-beam computed tomography for the assessment of residual lesions after primary treatment of proximal venous outflow obstructions. (February 2022) - Baccellieri, Domenico; Apruzzi, Luca; Ardita, Vincenzo; Bilman, Victor; De Cobelli, Francesco; Melissano, Germano; Chiesa, Roberto
Objective: Report the usefulness of completion cone-beam computed tomography (CBCT) as an adjunct tool during femoro-ilio-caval recanalization post stent placement. Methods: Data from patients who underwent complex endovenous recanalization for chronic proximal outflow obstruction from January 2018 to May 2020 were analyzed. Two groups of patients were obtained based on the execution or not of completion CBCT. Outcomes, radiation, and contrast doses in the two groups were compared. Results: Fifteen patients (9 female, mean age 46.9 ± 13.3) in the control group and ten patients (7 female, 58.3 ± 14) in the CBCT group were included. In the CBCT group, one patient underwent an intraprocedural revision due to a residual lesion. The median total kerma area product (KAPtotal ) and the total volume of contrast injected were not statistically different in the two groups. Conclusions: Completion CBCT after endovenous procedures might identify residual stenosis or stent malposition without a significant increase of total contrast injected and KAPtotal .